Impact of IFNL4 genetic variants on sustained virologic response and viremia in hepatitis C virus genotype 3 patients - Pedergnana, V; Irving, W; Barnes, E; McLauchlan, J; Spencer, C (Mary Ann Liebert, 2019)
Hepatitis C virus (HCV) genotype 3 is very prevalent in Europe and Asia and is associated with worst outcomes than other genotypes. Genetic factors have been associated with HCV infection; however, no extensive genome-wide study has been performed among HCV genotype 3 patients. In this study, using a large cohort of 1,759 patients infected with HCV genotype 3, we explore the role of genetic variants on the response to interferon (IFN) and direct-acting antiviral (DAA) regimens and viremia in a combined candidate gene and genome-wide analysis. We show that genetic variants within the IFN lambda 4 (IFNL4) locus are the major factors associated with the studied traits, accordingly with observations in other HCV genotypes and with comparable effect sizes. In particular, the functional dinucleotide polymorphism rs368234815 was associated with IFN-based sustained virologic response (SVR) [odds ratio (OR) = 1.5, P = 2.3 × 10-7], viremia (beta = -0.23, P = 8.8 × 10-10), and also DAA-based SVR (OR = 1.7; P = 4.2 × 10-4). Our results provide evidence for a role of genetic variants on HCV viremia and SVR, notably DAA-based, in patients infected with HCV genotype 3.